2000
DOI: 10.1118/1.598943
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared study of fluctuations in cerebral hemodynamics during rest and motor stimulation: Temporal analysis and spatial mapping

Abstract: We have noninvasively studied the motor cortex hemodynamics in human subjects under rest and motor stimulation conditions using a multichannel near‐infrared tissue spectrometer. Our instrument measures optical maps of the cerebral cortex at two wavelengths (758 and 830 nm), with an acquisition time of 160 ms per map. We obtained optical maps of oxy‐ and deoxy‐hemoglobin concentration changes in terms of amplitudes of folding average, power spectrum and coherence at the stimulation repetition frequency, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 31 publications
(58 reference statements)
7
120
1
Order By: Relevance
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…the "centered" Gamma function, has its peak located within the 30-50 mHz range (see Fig. 4), the narrow B-band should be related to taskrelated cognitive activity of the subject (Cordes et al, 2001;Toronov et al, 2000). The larger C-band is also assumed to carry cognitive activity related information, most probably due to the periodicity of the target stimuli sequence as we will explore more in detail in the next section.…”
Section: Interpretation Of the Canonical Bandsmentioning
confidence: 96%
See 2 more Smart Citations
“…In recent years many NIRS studies have demonstrated that cerebral hemodynamic changes associated with functional brain activity can be assessed noninvasively in adult human subjects (Benaron and Stevenson, 1994;Obrig et al, 2000). Several types of brain activity have been studied, including motor activity Colier et al, 1999;Toronov et al, 2000Toronov et al, , 2001Franceschini et al, 2000), visual activation (Ruben et al, 1997;Kato et al, 1993), auditory stimulation (Sakatani et al, 1999), and the performance of different cognitive tasks (Chance et al, 1993;Villringer et al, 1993). Kleinschmidt et al (1996) were first to measure simultaneously the BOLD fMRI signal and hemoglobin changes using NIRS.…”
Section: Introductionmentioning
confidence: 99%